2005
DOI: 10.18061/dsq.v25i1.527
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Medical Students About Communicating with Patients Who Have Sensory or Physical Disabilities

Abstract: No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The U.S. DOJ's "Access to medical care for individuals with mobility disabilities" [5] was published to help educate healthcare providers on how the ADA applies to healthcare facilities and services. Previous studies have shown that knowledge of the ADA and accessible equipment can reduce the number of barriers to healthcare [13,17]; unfortunately few training programs exist for healthcare professionals [18][19]. It is hoped that upon adoption, the U.S. Access Boards' new "Proposed accessibility standards for medical diagnostic equipment" [7] will provide healthcare facilities and clinics with specific accessible medical equipment standards and serve as a catalyst for development of professional training for healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…The U.S. DOJ's "Access to medical care for individuals with mobility disabilities" [5] was published to help educate healthcare providers on how the ADA applies to healthcare facilities and services. Previous studies have shown that knowledge of the ADA and accessible equipment can reduce the number of barriers to healthcare [13,17]; unfortunately few training programs exist for healthcare professionals [18][19]. It is hoped that upon adoption, the U.S. Access Boards' new "Proposed accessibility standards for medical diagnostic equipment" [7] will provide healthcare facilities and clinics with specific accessible medical equipment standards and serve as a catalyst for development of professional training for healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from this study and previous studies regarding health care professionals' knowledge of the ADA as it applied to their business environment are concerning but not surprising. Few educational programs exist that provide ADA or disability training for health professionals 24,45,[47][48][49][50] . This leaves practice administrators and other health professionals with little to no knowledge about how to best care for or accommodate their patients with disabilities 45,51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…To gather insights into training needs, we turned directly to students. Using similar methods as described elsewhere, 35 in February 2002, we conducted 2 focus group interviews with 13 total students nearing graduation and asked how they had been taught about communicating with persons with major mental illness.…”
Section: What Students Told Usmentioning
confidence: 99%